2014
DOI: 10.1002/pssr.201409475
|View full text |Cite
|
Sign up to set email alerts
|

Scanning photocurrent and PL imaging of a frozen polymer p-i-n junction

Abstract: Polymer light‐emitting electrochemical cells (LECs) are two‐terminal, solid state devices with a mixed ionic/electronic conductor as the active layer. Once activated by a DC voltage or current, a doping‐induced homojunction dictates the electrical and optical response of the LEC, making it highly unique and attractive among organic devices. However, the depletion width, a fundamental parameter of any semiconductor homojunction, has never been determined experimentally for a static LEC junction. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…This is in marked contrast to the PL profile of a real p-i-n junction. 58 The PL intensity of the p-doped region to the right is lower, as expected, but still at a significant level despite its dark appearance under UV illumination. The sensitivity of the PL scan is evident in the detection of a PL "transition zone" on the p side of the junction, between 0 and +30 µm.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…This is in marked contrast to the PL profile of a real p-i-n junction. 58 The PL intensity of the p-doped region to the right is lower, as expected, but still at a significant level despite its dark appearance under UV illumination. The sensitivity of the PL scan is evident in the detection of a PL "transition zone" on the p side of the junction, between 0 and +30 µm.…”
Section: Resultssupporting
confidence: 75%
“…Recently, we performed several OBIC studies of planar LECs with an interelectrode spacing ranging from 700 µm to 4.6 mm. [56][57][58] The extremely large gap size made it possible to perform OBIC scans using a variety of optical/cryogenic setups. The large planar cells were also easier to fabricate using shadow masking (vs. photolithographic) techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15] The developing p-i-n junction and the position of the zone where light is emitted (emission zone, EZ) can conveniently be followed by optical probing and photoluminescence experiments on so-called planar LECs that have a wide horizontal gap between the two electrodes. [6,[15][16][17][18][19][20][21][22][23][24] The summary of numerous studies is that the EZ in many cases is offcentred. In addition, it has been observed that the EZ is dynamic and shifts across the device until steady state is reached.…”
Section: Introductionmentioning
confidence: 99%
“…Time‐lapsed imaging of planar LECs establishes the fundamental operating mechanism of LECs: in situ electrochemical p‐ and n‐doping of the luminescent semiconductor, followed by light emission in the form of junction EL when the propagating doping fronts make contact to form a p‐n junction . It has been shown that the dynamic doping process involves the entire interelectrode gap, but the LEC junction occupies only a very narrow region between the p‐ and n‐doped neutral regions …”
Section: Introductionmentioning
confidence: 99%